A skeletal double gyroid formed by single coaxial bundles of catechol based bolapolyphiles. Issue 79 (19th September 2018) - Poppe, Silvio; Chen, Changlong; Liu, Feng; Tschierske, Carsten
Abstract : A new cubic phase is reported, formed by two networks of rod-bundles with one molecule length and containing discrete polar aggregates at the junctions. Abstract : A bolapolyphile, derived from a linear p -terphenyl core with glycerol groups at each end and two octadecyl chains fixed to the same side of the π-conjugated rod, is synthesized and is found to form a new type of self-assembled cubic LC phase with the Ia 3̄ d lattice. Each unit cell involves 16 polar aggregates interconnected by 24 coaxial rod-bundles at the single-molecule length, forming two interwoven skeletal networks with three-way junctions, being separated by a continuum of the lateral alkyl chains located around the gyroid minimal surface.